2012
DOI: 10.1063/1.4736727
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular-anisotropy CoFeB-MgO magnetic tunnel junctions with a MgO/CoFeB/Ta/CoFeB/MgO recording structure

Abstract: We investigated perpendicular CoFeB-MgO magnetic tunnel junctions (MTJs) with a recording structure consisting of two CoFeB-MgO interfaces, MgO/CoFeB (1.6 nm)/Ta (0.4 nm)/CoFeB (1.0 nm)/MgO. Thermal stability factor of MTJ with the structure having junction size of 70 nmφ was increased by a factor of 1.9 from the highest value of perpendicular MTJs with single CoFeB-MgO interface having the same device structure. On the other hand, intrinsic critical current for spin transfer torque switching of the double- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
158
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(163 citation statements)
references
References 31 publications
3
158
1
1
Order By: Relevance
“…[9,12] In addition, although the interfacial anisotropy in the out-of-plane devices measured by Tsunegi et al[11] can be as high as 3.3 mJ/m 2 , the effective perpendicular anisotropy was rather low (K e f f t ≈ 0.04mJ/m 2 ) relative to that of a Ta/CoFeB/MgO stack [3]. In this work, we explore the influence of Ta insertions within the CoFeB layer of MgO/CoFeB/MgO films by magnetometry and vector network analyzer ferromagnetic resonance (VNA-FMR) measurements.…”
mentioning
confidence: 99%
“…[9,12] In addition, although the interfacial anisotropy in the out-of-plane devices measured by Tsunegi et al[11] can be as high as 3.3 mJ/m 2 , the effective perpendicular anisotropy was rather low (K e f f t ≈ 0.04mJ/m 2 ) relative to that of a Ta/CoFeB/MgO stack [3]. In this work, we explore the influence of Ta insertions within the CoFeB layer of MgO/CoFeB/MgO films by magnetometry and vector network analyzer ferromagnetic resonance (VNA-FMR) measurements.…”
mentioning
confidence: 99%
“…The structure exhibits a moderate K eff ∼ 0.2 MJ m −3 , due to the competition between interface and shape anisotropy associated with the sizable magnetization. K eff can often be improved by introducing a second CoFeB/MgO interface in more complicated MgO/CoFeB/Ta/CoFeB/MgO structures [4]. Nevertheless, it has been shown that even the optimized MTJ structure is unstable for dimensions below 30 nm [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time that low switching current (45% decrease) and high interfacial PMA have been achieved simultaneously with double oxidation interfaces [50]. The same year, Sato et al [51] investigated MTJ with MgO/CoFeB/Ta/CoFeB/MgO free layer containing double CoFeB/MgO interfaces, which exhibited high thermal stability and comparable threshold currents. The thickness of Ta spacer layer was designed as 0.4 nm for the top and bottom CoFeB layers to form large enough exchange coupling, enabling the simultaneous STT switching of the two layers.…”
Section: Structure Optimization: Double Cofeb/mgo Interfacesmentioning
confidence: 99%